2019
DOI: 10.3390/ijms20235918
|View full text |Cite
|
Sign up to set email alerts
|

Waste Autochthonous Tuscan Olive Leaves (Olea europaea var. Olivastra seggianese) as Antioxidant Source for Biomedicine

Abstract: Olive leaf extract (OLE) can be obtained as biowaste and is extensively used a food supplement and an over-the-counter drug for its beneficial effects. New studies have investigated OLE concerning the role of oxidative stress in the pathogenesis of vascular disease. This in vitro study aims to evaluate if OLE extracted from the Tuscan Olea europaea protects endothelial cells against oxidative stress generated by reactive oxygen species (ROS). Methods: OLE total polyphenols (TPs) were characterized by the Folin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…The OLE used was extracted from Olea europaea var. Olivastra seggianese in Tuscan cultivar [ 45 ]. The antibacterial activity was evaluated in vitro against gram-negative E. coli and gram-positive S. aureus and L. innocua strains.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The OLE used was extracted from Olea europaea var. Olivastra seggianese in Tuscan cultivar [ 45 ]. The antibacterial activity was evaluated in vitro against gram-negative E. coli and gram-positive S. aureus and L. innocua strains.…”
Section: Resultsmentioning
confidence: 99%
“…The collection of the leaves from which OLE was extracted was performed at CNR-IVALSA, Follonica (GR), Italy. TP content was determined according to the Folin-Ciocalteu method using gallic acid as the standard equivalent (µg GAE/mg), purchased from Merk (Darmstadt, Germany) [ 45 ]. A high-performance liquid chromatography analysis (HPLC) was carried out to identify and quantify the major phenolic compounds of the obtained OLE.…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that these properties are related to the H-atom donation from the phenolic groups present in OL. For example, OL administration showed a protective effect against ROS production in endothelial cells since OL showed good cytocompatibility and antioxidant activity, which revealed effectiveness in controlling the oxidative stress upon exposure to H 2 O 2 [47]. In addition, OL presented slightly weaker radical scavenging activity than HTy by 2,7-dichlorodihydrofluorescein diacetate (DCFH-DA) and ABTS methods [48] and the ability to inhibit LDL oxidation by scavenging free radicals [49].…”
Section: Functional and Physiological Chemistry Of The Main Secoiridomentioning
confidence: 99%
“…These effects have been ascribed in part to their ability to act as potent antioxidants and scavengers of reactive oxygen species, generated under oxidative stress conditions and responsible for the onset of several inflammatory and degenerative diseases (9)(10)(11). These properties have therefore prompted the use of natural phenolic compounds not only as food supplements (7,(12)(13)(14)(15), but also as additives for functionalization of materials to be used e.g., in biomedicine (16)(17)(18), cosmetic (19)(20)(21)(22), or food industry (23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%